2010
DOI: 10.1523/jneurosci.1956-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Activation of Central Respiratory Chemoreceptor Neurons Involves Inhibition of a THIK-1-Like Background K+ Current

Abstract: At surgical depths of anesthesia, inhalational anesthetics cause a loss of motor response to painful stimuli (i.e., immobilization) that is characterized by profound inhibition of spinal motor circuits. Yet, although clearly depressed, the respiratory motor system continues to provide adequate ventilation under these same conditions. Here, we show that isoflurane causes robust activation of CO 2 /pH-sensitive, Phox2b-expressing neurons located in the retrotrapezoid nucleus (RTN) of the rodent brainstem, in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 35 publications
7
78
1
2
Order By: Relevance
“…Alternatively, such effects could be taking place in inhibitory interneurons that may express Kir3 channels. A recent study showed that isoflurane causes activation of some chemosensory neurons through inhibition of a THIK-1-like K 2 P channel that may be essential in maintaining some respiratory motor control during anesthesia (58). This presents another example of seemingly paradoxical potassium channel inhibi- tion by anesthetics, which may control a specific physiological response.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, such effects could be taking place in inhibitory interneurons that may express Kir3 channels. A recent study showed that isoflurane causes activation of some chemosensory neurons through inhibition of a THIK-1-like K 2 P channel that may be essential in maintaining some respiratory motor control during anesthesia (58). This presents another example of seemingly paradoxical potassium channel inhibi- tion by anesthetics, which may control a specific physiological response.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in anesthetized young rats in vivo these neurons do not show a decrease in discharge frequency after a dose of intravenous morphine sufficient to completely abolish phrenic nerve discharge (469). Similarly, 1-1.3 MAC isoflurane increased the discharge frequency of RTN neurons, likely by activating an unidentified kation channel and by inhibiting a leak K channel (THIK-1), while phrenic nerve discharge was depressed (369). On the other hand, intravenous chloralose-urethane depressed discharge of RTN neurons (369).…”
Section: Effects On Chemoreceptionmentioning
confidence: 97%
“…These clinical effects might result from a direct effect upon the pattern generator; alternatively, they could reflect decreased chemoreceptive inputs to the pattern generator (see below). It is important to note that, unlike propofol, volatile anesthetic agents do not themselves result in apnea, an effect likely due to activation of RTN neurons [36].…”
Section: Inhalational Anestheticsmentioning
confidence: 99%